(untitled) (Journal of Science and Technology Research, 2023)
This study was conducted to evaluate the synergistic effects of the mixtures of green silver nanoparticles (AgNPs) with ampicillin and metformin separately in obviating the global threats of antimicrobial resistance and diabetes mellitus. AgNPs was synthesized using Azadirachta indica aqueous leaf extract at varying extract concentration and incubation time. The synthesis of AgNPs in aqueous solution was confirmed by the visual color change and by using a UV-Vis spectrophotometer. The biosynthesized AgNPs was further characterized using Scanning Electron Microscope (SEM) analysis. The experimental results revealed that the biosynthesized AgNPs were polydispersed, smaller in size and aggregated. The mean diameter of the formed AgNPs was 50 nm as evident from the SEM analysis. Additionally, the mixtures of AgNPs with ampicillin and metformin exhibited synergistic in vitro antimicrobial and in vivo antidiabetic effects i.e., being more efficacious than AgNPs, ampicillin and metformin alone. J. of Sci. and Tech. Res. 4(1): 91-100, 2022